English: English - Raldi, LD Muhammad; Damayanti, Setia; Ridwan, Ridwan (Jurnal Teknik Mesin Mechanical Xplore, 2025)
Sustainable waste management and environmentally friendly production systems have become central to modern supply chain practices. Refuse-derived fuel, an alternative fuel derived from solid waste, presents significant potential in supporting green supply chain management principles. However, its integration into the green supply chain management framework remains fragmented. This study aims to explore the integration of refuse-derived fuel into sustainable supply chain management using an integrative literature review method. Findings indicate that refuse-derived fuel contributes not only to reducing landfill volume and emissions but also enhances energy efficiency, particularly in the cement manufacturing industry. Key challenges include feedstock quality, technological complexity, and limited policy support. This study proposes a conceptual model positioning refuse-derived fuel as a strategic driver for green production. Through a multidisciplinary understanding of refuse-derived fuel, waste management, and supply chain innovation, refuse-derived fuel emerges as a promising component for systematic integration into sustainable production and circular economy strategies. Future research is recommended to validate this conceptual model empirically and to explore practical implementation pathways in various industrial sectors.